Slide68.JPG

Slide69.JPG
Slide70.JPG

Slide71.JPG Slide72.JPG Slide73.JPG

 

  1. Chapter 13 Class 11 Limits and Derivatives
  2. Serial order wise

Transcript

Example 20 Find the derivative of f(x) from the first principle, where f(x) is (i) sin x + cos x Given f (x) = sin x + cos x We need to find Derivative of f(x) We know that f’(x) = lim┬(hβ†’0) 𝑓⁑〖(π‘₯ + β„Ž) βˆ’ 𝑓(π‘₯)γ€—/β„Ž Here, f (x) = sin x + cos x f (x + h) = sin (x + h) + cos (x + h) Putting values f’(x) = lim┬(hβ†’0)⁑〖(sin⁑〖(π‘₯ + β„Ž)γ€— + cos⁑(π‘₯ + β„Ž) βˆ’ (sin⁑π‘₯ + cos⁑〖π‘₯)γ€—)/β„Žγ€— Using sin (A + B) = sin A cos B + cos A sin B & cos (A + B) = cos A cos B – sin A sin B = lim┬(hβ†’0)⁑〖sin⁑〖π‘₯ cosβ‘γ€–β„Ž +γ€– cos〗⁑〖π‘₯ sinβ‘γ€–β„Ž + cos⁑〖π‘₯ cosβ‘γ€–β„Ž βˆ’ sin⁑〖π‘₯ γ€– sinγ€—β‘γ€–β„Ž βˆ’γ€– sin〗⁑〖π‘₯ βˆ’γ€– cos〗⁑π‘₯ γ€— γ€— γ€— γ€— γ€— γ€— γ€— γ€— γ€—/hγ€— = lim┬(hβ†’0)⁑〖cos⁑〖π‘₯ sinβ‘γ€–β„Ž βˆ’γ€– sin〗⁑〖π‘₯ sinβ‘γ€–β„Ž + sin⁑〖π‘₯ cosβ‘γ€–β„Ž βˆ’ sin⁑〖π‘₯ +γ€– cos〗⁑〖π‘₯ cosβ‘γ€–β„Ž βˆ’γ€– cos〗⁑π‘₯ γ€— γ€— γ€— γ€— γ€— γ€— γ€— γ€— γ€—/hγ€— = lim┬(hβ†’0)⁑〖sinβ‘γ€–β„Ž γ€–(cos〗⁑〖π‘₯ βˆ’ sin⁑〖π‘₯) + sin⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’ 1) + cos⁑π‘₯ (cosβ‘γ€–β„Ž βˆ’ 1)γ€— γ€— γ€— γ€— γ€— γ€—/hγ€— = lim┬(hβ†’0)⁑(sinβ‘γ€–β„Ž γ€–(cos〗⁑〖π‘₯ βˆ’ sin⁑〖π‘₯)γ€— γ€— γ€—/h+sin⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’ 1)γ€— γ€—/h+cos⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’ 1)γ€— γ€—/β„Ž)" " = lim┬(hβ†’0)⁑〖sinβ‘γ€–β„Ž γ€–(cos〗⁑〖π‘₯ βˆ’γ€– sin〗⁑〖π‘₯)γ€— γ€— γ€—/h+lim┬(hβ†’0) sin⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’ 1)γ€— γ€—/h+lim┬(hβ†’0) cos⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’ 1)γ€— γ€—/β„Žγ€— = lim┬(hβ†’0)⁑〖"(cos x – sin x)" sinβ‘β„Ž/β„Ž+lim┬(hβ†’0) "(– sin x)" ((1 βˆ’ cosβ‘γ€–β„Ž)γ€—)/β„Žγ€—+lim┬(hβ†’0) "(– cos x)" ((1 βˆ’ cosβ‘γ€–β„Ž)γ€—)/β„Ž = "(cos x – sin x)" (π₯𝐒𝐦)┬(π‘β†’πŸŽ)⁑〖𝐬𝐒𝐧⁑𝒉/π’‰βˆ’sin⁑〖π‘₯ (π₯𝐒𝐦)┬(π‘β†’πŸŽ) γ€— ((𝟏 βˆ’ 𝒄𝒐𝒔⁑〖𝒉)γ€—)/π’‰βˆ’cos⁑π‘₯ (π₯𝐒𝐦)┬(π‘β†’πŸŽ) ((𝟏 βˆ’ 𝒄𝒐𝒔⁑〖𝒉)γ€—)/𝒉〗Using (π‘™π‘–π‘š)┬(β„Žβ†’0) π‘ π‘–π‘›β‘β„Ž/β„Ž = 1 & (π‘™π‘–π‘š)┬(β„Žβ†’0) γ€–(1 βˆ’ π‘π‘œπ‘ γ€—β‘γ€–β„Ž)γ€—/β„Ž = 0 Using (π‘™π‘–π‘š)┬(β„Žβ†’0) π‘ π‘–π‘›β‘β„Ž/β„Ž = 1 & (π‘™π‘–π‘š)┬(β„Žβ†’0) γ€–(1 βˆ’ π‘π‘œπ‘ γ€—β‘γ€–β„Ž)γ€—/β„Ž = 0 Example 20 Find the derivative of f(x) from the first principle, where f(x) is (ii) x sin x Given f (x) = x sin x We need to find Derivative of f(x) We know that f’(x) = lim┬(hβ†’0) 𝑓⁑〖(π‘₯ + β„Ž) βˆ’ 𝑓(π‘₯)γ€—/β„Ž Here, f (x) = x sin x So, f (x + h) = (x + h) sin (x + h) Putting values f’(x) =lim┬(hβ†’0) ((π‘₯ + β„Ž) sin⁑〖 (π‘₯ + β„Ž) βˆ’ π‘₯ sin⁑〖π‘₯ γ€— γ€—)/β„Ž Using sin (A + B) = sin A cos B + cos A sin B = lim┬(hβ†’0)⁑〖((π‘₯ + β„Ž)(sin⁑〖π‘₯ cosβ‘γ€–β„Ž +γ€– cos π‘₯〗⁑sinβ‘γ€–β„Ž γ€— )γ€— βˆ’ π‘₯ sin⁑π‘₯ γ€—)/β„Žγ€— = lim┬(hβ†’0)⁑〖(π‘₯(sin⁑〖π‘₯ cosβ‘γ€–β„Ž +γ€– cos〗⁑〖π‘₯ sinβ‘γ€–β„Ž) + β„Ž (sin⁑〖π‘₯ cosβ‘γ€–β„Ž +γ€– cos〗⁑〖π‘₯ sinβ‘γ€–β„Ž) βˆ’ π‘₯ sin⁑π‘₯ γ€— γ€— γ€— γ€— γ€— γ€— γ€— γ€—)/β„Žγ€— = lim┬(hβ†’0)⁑〖(π‘₯ sin⁑〖π‘₯ cosβ‘γ€–β„Ž + π‘₯ cos⁑〖π‘₯ sinβ‘γ€–β„Ž + β„Ž γ€–(sin〗⁑〖π‘₯ cosβ‘γ€–β„Ž + cos⁑〖π‘₯ sinβ‘γ€–β„Ž) βˆ’ π‘₯ sin⁑π‘₯ γ€— γ€— γ€— γ€— γ€— γ€— γ€— γ€—)/β„Žγ€— = lim┬(hβ†’0)⁑〖(π‘₯𝑠𝑖𝑛 π‘₯ cosβ‘γ€–β„Ž βˆ’ π‘₯ sin⁑〖π‘₯ + π‘₯ cos⁑〖π‘₯ sinβ‘γ€–β„Ž + β„Ž(sin⁑〖π‘₯ cosβ‘γ€–β„Ž + cos⁑〖π‘₯ sinβ‘β„Ž γ€— γ€—)γ€— γ€— γ€— γ€— γ€—)/β„Žγ€— = lim┬(hβ†’0)⁑〖(π‘₯𝑠𝑖𝑛 π‘₯ γ€–(cosγ€—β‘γ€–β„Ž βˆ’ 1)+ π‘₯ cos⁑〖π‘₯ sinβ‘γ€–β„Ž + β„Ž(sin⁑〖π‘₯ cosβ‘γ€–β„Ž + cos⁑〖π‘₯ sinβ‘β„Ž γ€— γ€—)γ€— γ€— γ€— γ€—)/β„Žγ€— = lim┬(hβ†’0)⁑((π‘₯ sin⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’1)γ€— γ€—)/β„Ž+(π‘₯ cos⁑〖π‘₯ sinβ‘β„Ž γ€—)/β„Ž+(β„Ž (sin⁑〖π‘₯ cosβ‘γ€–β„Ž +cos⁑〖π‘₯ sinβ‘γ€–β„Ž)γ€— γ€— γ€— γ€—)/β„Ž) = lim┬(hβ†’0)⁑〖〖x sin〗⁑〖π‘₯ (cosβ‘γ€–β„Ž βˆ’1)γ€— γ€—/β„Ž+lim┬(hβ†’0) (π‘₯ cos⁑〖π‘₯ sinβ‘β„Ž γ€— )/h+lim┬(hβ†’0) (sin⁑〖π‘₯ cosβ‘γ€–β„Ž +cos⁑〖π‘₯ sinβ‘γ€–β„Ž )γ€— γ€— γ€— γ€— γ€— = lim┬(hβ†’0)⁑〖π‘₯ sin⁑〖π‘₯ ((cosβ‘γ€–β„Ž βˆ’1)γ€—)/β„Žγ€—+lim┬(hβ†’0) π‘₯ cos⁑π‘₯ sinβ‘β„Ž/h+lim┬(hβ†’0) (sin⁑〖π‘₯ cosβ‘γ€–β„Ž +cos⁑〖π‘₯ sinβ‘γ€–β„Ž )γ€— γ€— γ€— γ€— γ€— = – x sin x (π₯𝐒𝐦)┬(π‘β†’πŸŽ) ((πŸβˆ’γ€– 𝒄𝒐𝒔〗⁑〖𝒉)γ€—)/𝒉+π‘₯ cos⁑〖π‘₯ (π₯𝐒𝐦)┬(π‘β†’πŸŽ) π’”π’Šπ’β‘π’‰/𝐑+γ€— lim┬(hβ†’0) (sin⁑〖π‘₯ cosβ‘γ€–β„Ž +cos⁑〖π‘₯ sinβ‘γ€–β„Ž )γ€— γ€— γ€— γ€— Using (π‘™π‘–π‘š)┬(β„Žβ†’0) π‘ π‘–π‘›β‘β„Ž/β„Ž = 1 & (π‘™π‘–π‘š)┬(β„Žβ†’0) γ€–(1 βˆ’ π‘π‘œπ‘ γ€—β‘γ€–β„Ž)γ€—/β„Ž = 0 = – x sin x (0) + x cos x (1) + ( sin x cos 0 + cos x sin 0) = 0 + x cos x + sin Γ— 1 + cos x Γ— 0 = 0 + x cos x + sin x + 0 = x cos x + sin x Hence f’ (x) = x cos x + sin x

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.